Cafishin' - Purcell, Braden (My University, 2022)
Catfishin' is an interactive fishing game developed in the Unity Engine with C# from Microsoft Visual Studio. In the game, there are over 100 different unique fish that the player can collect and display in their inventory. The game evokes a relaxing feeling from the background music and the art style that pairs very well with the rhythm-based catching mechanic. When the player casts their line, a fish bites on and the catching sequence begins. In tandem with the music playing in the background, the player must respond to notes on the screen to catch the fish. Once the fish is caught, the player can review that fish in their inventory and can continue fishing to complete various tasks. Since what we have done of Catfishin' is largely a sophisticated and bug-free prototype, there is a lot of room for growth and improvement. We plan to make more detailed tasks and an achievement system. We plan to make the environment in which the player can fish more interactive with new characters. Additionally, we plan to add more variety to the catching sequence, with various new melodies and rhythm components to correspond to the wide variety of fish that we already have in the game. Lastly, we plan for there to be a currency component in place to reward players for selling the fish that they catch, completing daily tasks, and completing long achievement rewards. With this currency system in place, we will be able give the player visual upgrades to their character so the best Catfishermen can show it off in a great way. With new environments and new features, we believe Catfishin' will be a one-of-a-kind. relaxing, and fun game that everyone can enjoy.